2010
DOI: 10.1590/s0103-84782010005000117
|View full text |Cite
|
Sign up to set email alerts
|

Inibição da ação do etileno retarda o desenvolvimento de injúrias de frio em tangor 'Murcott'

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
5
0
4
Order By: Relevance
“…On the other hand, Edagi et al (2010) found that respiratory activity in the tangor cv. Murcote (Citrus reticulate x Citrus sinensis), did not vary significantly after treatment with 1-MCP, when compared to the control fruit.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Edagi et al (2010) found that respiratory activity in the tangor cv. Murcote (Citrus reticulate x Citrus sinensis), did not vary significantly after treatment with 1-MCP, when compared to the control fruit.…”
Section: Resultsmentioning
confidence: 99%
“…Em nêsperas, (Eriobotrya japonica Lindl. ), o estresse desencadeado pelo frio pode ocasionar o enrijecimento e o escurecimento interno da polpa e também aumentar a suscetibilidade aos fungos (Cai et al, 2006;Edagi et al, 2009). O aparecimento desses danos deprecia a qualidade e resulta em sérias implicações à comercialização e aceitação dos frutos pelos consumidores.…”
Section: Salicylates Compounds and The Loquat Fruit Tolerance To Chilunclassified
“…O aparecimento desses danos deprecia a qualidade e resulta em sérias implicações à comercialização e aceitação dos frutos pelos consumidores. Por esta razão, diversos tratamentos têm sido testados para evitar ou diminuir o aparecimento desses danos em nêsperas e outras espécies sensíveis ao frio (Cai et al, 2006;Edagi et al, 2009Edagi et al, , 2010Sestari et al, 2010).…”
Section: Salicylates Compounds and The Loquat Fruit Tolerance To Chilunclassified
See 2 more Smart Citations